Estradiol-17ß Is Influenced by Age, Housing System, and Laying Performance in Genetically Divergent Laying Hens (Gallus gallus f.d.) - Mehlhorn, Julia; Höhne, Anja; Baulain, Ulrich; Schrader, Lars; Weigend, Steffen; Petow, Stefanie (Frontiers in Physiology, 2022)
The estrogen estradiol-17ß is known as one of the major gonadal steroid hormones with different functions in reproduction. In this study we analyzed estradiol-17ß concentration in laying hens of four pure bred chicken laying lines at four different time intervals of the laying period (17th to 19th week of age, 33rd to 35th week of age, 49th to 51st week of age and 72nd week of age). The high performing white egg (WLA) and brown egg (BLA) layer lines as well as the low performing white (R11) and brown (L68) layer lines were kept in both single cages and a floor housing system. We investigated whether there were differences in estradiol concentrations between lines at different ages that could be related to selection for high egg production or phylogenetic origin of the animals, and whether there was an influence of housing conditions on estradiol-17ß. Estradiol-17ß concentrations differed between high and low performing layer lines at all time intervals studied. High performing hens showed higher estradiol-17ß concentrations compared to low performing hens. In all lines, highest estradiol-17ß concentration was measured at their 49th to their 51st week of age, whereas the peak of laying intensity was observed at their 33rd to their 35th week of age. Additionally, hens with fewer opportunities for activity housed in cages showed higher estradiol-17ß concentrations than hens kept in a floor housing system with more movement possibilities. We could show that laying performance is strongly linked with estradiol concentration. This concentration changes during laying period and is also influenced by the housing system.